SEED POTATOES HARVESTING AND TRANSPORTATION TECHNOLOGY - M. L. Kryukov; V. N. Zernov; G. A. Kalinkin; M. V. Ivanov; A. S. Rumyantsev; L. N. Kynev (Сельскохозяйственные машины и технологии, 2017)
When engineering potatoes harvesting procedure for its optimization it is important to calculate precisely the quantity of machines, containers and workers who will be involved in harvesting process. This depends on the acreage and productivity. An output yield should be harvested in predetermined terms. Harvesting and transportation of potatoes in bags is obsolete technology which complicates and slows down process of harvest and transport operations. Agrarian introduce mechanization to reduce the level of manual work use or to exclude it completely. The authors offered container technology of harvesting, transportation and sorting of seed potatoes. The containers having identical amount and load-carrying capacity were made of different materials for check of this technology. Branded structure of the machines which can be used at harvesting was established. The main specifications were indicated. The authors determined shortcomings of the soft bags for potatoes harvesting and brought into focus benefits of containers use. The exact quantity of containers and machines for potatoes harvesting in the OOO Redkinskoye APC (Tver region) was calculated. The seed potatoes are grown there on 2.43 hectares. The time frames of harvesting were determined.